The role of electron-scale turbulence in the JET tokamak: experiments and modelling. (2nd August 2021) - Mantica, P.; Bonanomi, N.; Mariani, A.; Carvalho, P.; Delabie, E.; Garcia, J.; Hawkes, N.; Johnson, T.; Keeling, D.; Sertoli, M.; Staebler, G.M.; Szepesi, G.; et al.
Abstract: Dedicated electron heat transport experiments have been carried out in L- and H-mode Deuterium plasmas of the JET-ILW tokamak to identify the amount of electron heat carried by electron-scale electron temperature gradient (ETG) modes. Ion cyclotron resonance heating at different positions has been used to probe the response of the electron temperature inverse gradient length R / L Te to changes in electron heat flux q e, while different amounts of neutral beam heating allowed to scan the ratio of ion to electron temperature T e / T i, which is a key parameter for the onset of ETGs. Results indicate a steepening of the normalized q e vs R / L Te curve above R / L Te ∼ 8 for T e / T i ⩽ 1, suggestive of the ETG onset. Ion-scale gyro-kinetic (GK) simulations match the ion heat flux and the low- R / L Te part of the q e curve, but do not reproduce such steepening at high R / L Te . Multi-scale GK simulations covering both ion and electron scales and including one impurity bundling light and heavy species indicate an ETG contribution only for R / L Te values larger than the experimental ones. Sensitivity studies of such result are difficult to achieve due to limitation in numerical resources. The quasi-linear TGLF model has been used for sensitivity studies. With the same bundled impurity as the GK multi-scale, TGLF shows the q e steepening at much larger R / L Te values than in experiment, but when using the real mix of light impurities neglecting the heavy impurities, TGLF gets closer to the experimental results. Profile simulations with TGLF including both light and heavy impurities show over-prediction of T e profiles and in some cases also of density, but good T i predictions, confirming issues with the model electron stiffness for these plasmas.